Highly Electrically Conductive Flexible Ionogels by Drop‐Casting Ionic Liquid/PEDOT:PSS Composite Liquids onto Hydrogel Networks. Issue 1 (1st November 2021) - Yang, Jianmin; Chang, Li; Ma, Chuao; Cao, Ziquan; Liu, Hongliang
Abstract: Ionogels have been extensively studied as ideal flexible and stretchable materials by virtue of the unique properties of ionic liquids, such as non‐volatility, non‐flammability, and negligible vapor pressure. However, the generally low ionic conductivity of the current ionogels limits their applications in the market of highly conductive, flexible, and stretchable electrical devices. Here, the fabrication of highly electrically conductive ionogels is reported by combining composite liquids consisting of 1‐ethyl‐3‐methylimidazolium dicyanamide ([EMIM][DCA]) and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) with flexible negative‐charged poly(2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid) (PAMPS) hydrogel. The generated composite film exhibits high electrical conductivity up to about 38 S cm −1 with the maximum tensile strain of 45% and fracture stress of 27 kPa. In addition, it is demonstrated that the composite film can maintain conductivity in a high level under different mechanical deformations, and can also be used as flexible sensors in a wide temperature range from −58 to 120 ℃. It is believed that the designed composite film would expand the applications of flexible conductive materials where both high conductivity and robust mechanical flexibility are required. Abstract : A [EMIm][DCA]‐IL/PEDOT:PSS@[EMIm][DCA]‐ PAMPS (P@P) composite ionogel film, fabricated by combining composite liquids consisting of 1‐ethyl‐3‐methylimidazolium dicyanamide ([EMIM][DCA]) and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) with flexible negative‐charged poly(2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid) (PAMPS) hydrogel, exhibits high electrical conductivity about 38 S cm −1 with excellent flexibility.